The NBN Futures Forum: Social and Economic Benefits of Broadband for Digital Inclusion and Telehealth - Campbell, Leith H; Smith, Anthony C.; Brooks, Peter (Journal of Telecommunications and the Digital Economy, 2020)
On 18 August 2020, TelSoc hosted the fourth NBN Futures Forum, held online, on the theme of social and economic benefits of broadband. Three speakers discussed various aspects of the topic, including the need for universal digital inclusion, the benefits of healthcare delivery via telehealth, and the actions required of government to support telehealth availability. Discussion following the speeches emphasised the need for universal access to broadband and telehealth services to improve access to health providers and, through education, reduce social inequities and overcome some social determinants of poor health outcomes.